Supramolecular gels derived from biomolecules - Poimala, Milka (2021)
This Bachelor’s thesis consists of a literature part and an experimental part. The literature part first presents the terminology of supramolecular chemistry followed by the concept of a supramolecular gel. After introducing selected biomolecules, some applications based on supramolecular gels derived from them are reviewed. In the experimental part the gel formation abilities of three bile acid derivatives were examined.